A Study of The Variation of Price-Earnings with Intrinsic Market Value Indicators - Mlilo, Mncedisi (My University, 2011)
In the last few years, there has been lively debate about the appropriateness of financial ratios in determining the value of high technology stocks especially in the US market. Of particular focus in this debate has been the high to very high P-E ratios assigned to companies that by any other measure seemed to be performing poorly. There is a need for an analysis that considers the whole market, rather than segmenting it, and that attempts to establish relationships based on intrinsic value indicators of companies. The reason for considering the whole market is to gain a market wide perspective, thus avoiding the peculiarities of segments of the market. There is also a need to do this, specifically, in the context of the JSE. In trying to address the points raised above, this report set out to determine the relationship between different levels of P-E ratio values and Percentage Sales Growth, as well as the value addition spread for the JSE. The difference between the return on invested capital and the capitalization rate was used as the value addition spread, since it provides an unbiased measure of the use of deployable capital. The findings of the report were that the relationship between these variables is obscure and cannot be captured in a iii multiple regression relationship. The conclusion arrived at was that the relationship between the P-E ratio and intrinsic market value indicators is not apparent in the South African environment.
MBA thesis - WBS
Keywords: Financial ratios; Share market